Improved gross efficiency during long duration submaximal cycling following a short-term high carbohydrate diet - Cole, M.; Coleman, D.; Hopker, J.; Wiles, J. (International Journal of Sports Medicine, 2014)
To assess the effect of dietary manipulation on gross efficiency (GE), 15 trained male cyclists completed 3×2 h tests at submaximal exercise intensity (60% Maximal Minute Power). Using a randomized, crossover design participants consumed an isoenergetic diet (~4 000 kcal.day-1) in the 3 days preceding each test, that was either high in carbohydrate (HighCHO, [70% of the total energy derived from carbohydrate, 20% fat, 10% protein]), low in carbohydrate (LowCHO, [70% fat, 20% carbohydrate, 10% protein]) or contained a moderate amount of carbohydrate (ModCHO, [45% carbohydrate, 45% fat, 10% protein]). GE along with blood lactate and glucose were assessed every 30 min, and heart rate was measured at 5 s intervals throughout. Mean GE was significantly greater following the HighCHO than the ModCHO diet (HighCHO=20.4%±0.1%, ModCHO=19.6±0.2%; P<0.001). Additionally, HighCHO GE was significantly greater after 25 min (P=0.015) and 85 min (P=0.021) than in the LowCHO condition. Heart rate responses in the HighCHO condition were significantly lower than during the LowCHO tests (P=0.005). Diet had no effect on blood glucose or lactate (P>0.05). This study suggests that before the measurement of gross efficiency, participants` diet should be controlled and monitored to ensure the validity of the results obtained.